Influence of the Oil Phase on the Microencapsulation by Complex Coacervation. (23rd June 2015) - Prata, Ana S.; Grosso, Carlos R.F.
Abstract: The influence of oil type on the process yield, efficiency of encapsulation, particle size and morphological aspects of coacervated microparticles was investigated. Firstly, several factors affecting microencapsulation of oils by complex coacervation were simultaneously examined. The results indicated that the process yield is mainly dependent on the velocity of homogenization, temperature and polymer ratio. Using optimum conditions for producing microparticles [pH 4.0, 14, 000 rpm, 50 °C, gelatin:gum arabic (GE:GA) 1:1 and 2.5 % w/v], different core materials were tested: a vegetable oil (almond oil), an oil with higher hydrophilic lipophilic balance (vetiver essential oil) and a highly hydrophobic oil (mineral oil). The oil phase exerted an influence on microparticle formation, disturbing the complexation of polymers and modifying the core distribution within the particles. Some of the polymers were complexed when mineral oil was used, and the highest efficiency of encapsulation (91.8 %) was obtained with vetiver oil, followed by the almond (70.6 %) and mineral (38.0 %) oils. Particles produced with vetiver oil were larger (43.5 μm) than those produced with mineral oil (35.0 μm) and almond oil (19.2 μm), and the increase in the size is due to the encapsulation of many small droplets of emulsion, characterizing these particles as multinucleate ones.